Enhancing Students’ Speaking Skills through the Analysis of Intrinsic Motivation in Using English - Vijaya, Rosyidah Jayanti; Nurharjanti, Marita; Wibowo, Hermenegildus Agus (BHATARA: Jurnal Multidisiplin Ilmu, 2024)
Speaking skills have always been exacting for EFL students in language learning. Intrinsic motivation is said to play an important role in shaping students’ speaking skills. This study aimed to examine the influence of students’ intrinsic motivations on their English-speaking skills. By conducting descriptive quantitative research, data was gathered and processed for data coding, data analysis of normality test, validity and reliability test to get the results. A survey of 128 students explored two dimensions of the Intrinsic Motivation Inventory (IMI) covering students’ interest/enjoyment and perceived competence. The questionnaire that was coded and put into the Linkert Scale also involved reverse-coded questions to validate other questions. The result indicated a significant influence of students’ interest/enjoyment and perceived competence in using English on students’ speaking skills. The results are expected to help students and teachers in terms of student engagement in the classroom. Keywords: Speaking Skills, Intrinsic Motivation, Interest/Enjoyment, Perceived Competence, Multiple Regression Analysis